Local scour below a submerged low weir - Yeo, Sean Teck Hin (Nanyang Technological University, 2024)
Scour, a significant concern in hydraulic engineering, particularly around hydraulic structures, poses challenges to infrastructure stability and safety. This study presents a comprehensive investigation into the phenomenon of local scour below a submerged low weir, focusing on the determination of maximum scour depth. The Schoklitsch formula and empirical equations are employed for scour depth prediction, supplemented by numerical modeling techniques. Results are scrutinized for jet flipping phenomena and scour profile dimensions, contributing to a deeper understanding of scour processes, and informing engineering practices for infrastructure design and risk mitigation. The study not only contributes to a deeper understanding of scour processes but also holds significant implications for engineering practices. By unraveling the intricate mechanisms underlying scour phenomena, we pave the way for informed infrastructure design and effective risk mitigation strategies, thus ensuring the resilience and longevity of hydraulic structures in the face of scour challenges.